Obstacles to prompt and effective malaria treatment lead to low community-coverage in two rural districts of Tanzania - Dillip Angel; Nathan Rose; Msechu June J; Lengeler Christian; Obrist Brigit; Hetzel Manuel W; Makemba Ahmed M; Mshana Christopher; Schulze Alexander; Mshinda Hassan (BMC, 2008)
Abstract Background Malaria is still a leading child killer in sub-Saharan Africa. Yet, access to prompt and effective malaria treatment, a mainstay of any malaria control strategy, is sub-optimal in many settings. Little is known about obstacles to treatment and community-effectiveness of case-management strategies. This research quantified treatment seeking behaviour and access to treatment in a highly endemic rural Tanzanian community. The aim was to provide a better understanding of obstacles to treatment access in order to develop practical and cost-effective interventions. Methods We conducted community-based treatment-seeking surveys including 226 recent fever episodes in 2004 and 2005. The local Demographic Surveillance System provided additional household information. A census of drug retailers and health facilities provided data on availability and location of treatment sources. Results After intensive health education, the biomedical concept of malaria has largely been adopted by the community. 87.5% (78.2-93.8) of the fever cases in children and 80.7% (68.1-90.0) in adults were treated with one of the recommended antimalarials (at the time SP, amodiaquine or quinine). However, only 22.5% (13.9-33.2) of the children and 10.5% (4.0-21.5) of the adults received prompt and appropriate antimalarial treatment. Health facility attendance increased the odds of receiving an antimalarial (OR = 7.7) but did not have an influence on correct dosage. The exemption system for under-fives in public health facilities was not functioning and drug expenditures for children were as high in health facilities as with private retailers. Conclusion A clear preference for modern medicine was reflected in the frequent use of antimalarials. Yet, quality of case-management was far from satisfactory as was the functioning of the exemption mechanism for the main risk group. Private drug retailers played a central role by complementing existing formal health services in delivering antimalarial treatment. Health system factors like these need to be tackled urgently in order to translate the high efficacy of newly introduced artemisinin-based combination therapy (ACT) into equitable community-effectiveness and health-impact.